Knowledge, attitude and practice of cigarette smoking among university students in Muzaffarabad, Pakistan: a cross-sectional study - Latif, Zahid; Jamshed, Junaid; Khan, Muhammad Mushtaq (International Journal of Scientific Reports, 2017)
Background: Smoking is the leading cause of morbidity and mortality worldwide. Smoking killed more than 6 million people, about 80% in the developing countries such as Pakistan in 2011. Now it has become major public health issue in the world. Methods: A descriptive cross-sectional study was conducted among 542 students at University of Azad Jammu and Kashmir in Muzaffarabad, Pakistan from July to December 2015. The data were collected using a pre-tested, self-administered, validated questionnaire requiring information about socio-demographic characteristics, practice and patterns of cigarette smoking, knowledge about its harmful effects and attitude towards smoking control and prevention measures. Results: The prevalence of cigarette smoking among students was 49.5%. The mean age for starting cigarette smoking was 19.2±2.73 years. Cigarette smoking constituted 61.3% and shisha constituted 18.4%. The main reason for cigarette smoking was peer pressure (35.0%) followed by family influencing (24.5%). About 79.5% of the smokers had intension to quit smoking. There was no significant difference (p value=0.484) between prevalence of cigarette smoking in different faculties of University of Azad Jammu and Kashmir. The majority of the students (84.3%) knew that smoking is harmful for their health. However, rates of non-smoking students who knew the adverse effects of smoking were significantly higher than that of students who smoke. A high rate of students showed positive attitude towards smoking prevention and control measures. Conclusions: High prevalence of cigarette smoking was reported among students. There is a need to implement an anti-smoking program among students at University of Azad Jammu and Kashmir.